Maximizing the value of generation Z in the workplace by knowing their communication habits and attitudes - Low, Cui Bun (2023)
Generation Z is the future of society; it is critical to understand the characteristics of this group of people. As their entrance into the workplace has raised the competition between different generations of colleagues, this may cause a huge gap between other generations with them. The objectives of this study were to identify the communication habits and attitudes of Generation Z in the workplace and to find out the most effective way to maximize the value of Generation Z in the workplace. In this study, a quantitative research method was adopted, and 101 respondents participated in this study. The collected data was analyzed using Cronbach Alpha in the SPSS system. Besides, this study revealed that one of Generation Z’s workplace communication habits and attitudes is that feedback from higher management is important, while the leadership, and being recognized and appreciated by the organization are the ways that can maximize the value of Generation Z in the workplace. In conclusion, to get along with Generation Z in the workplace, using the appropriate way to develop their potential is essential.